2021
DOI: 10.1002/suco.202100021
|View full text |Cite
|
Sign up to set email alerts
|

Using calcium‐rich precursors to improve the early‐compressive strength of alkali‐activated slag cement at low temperature

Abstract: This study examines the potential of using calcium-rich precursors to improve the strength of alkali-activated slag (AAS) cement at low temperature. To achieve this target, the effect of calcium-rich precursors on the early strength development of AAS mortars cured at 5 C was assessed. The strength development was investigated along with its internal temperature, microstructure and reaction products. It is found that the calcium-rich precursors can improve the early strength of AAS around 35% and the group wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 43 publications
(111 reference statements)
0
1
0
Order By: Relevance
“…The setting time is also one of the important workability properties of concrete mixes, which determines the time window for mixing, transporting and placing the mixes. One of the disadvantages of applying GGBFS as a precursor in alkali activated cementitious materials is its rapid setting time [32][33][34][35], especially when mixed with more activator to obtain higher mechanical properties [36], its setting is extremely rapid, making it extremely limited in practical engineering applications [37]. You N et al [38] found that the amount of steel slag at 50% can significantly delay the setting time of alkali activated mortar and improve the flowability.…”
Section: Introductionmentioning
confidence: 99%
“…The setting time is also one of the important workability properties of concrete mixes, which determines the time window for mixing, transporting and placing the mixes. One of the disadvantages of applying GGBFS as a precursor in alkali activated cementitious materials is its rapid setting time [32][33][34][35], especially when mixed with more activator to obtain higher mechanical properties [36], its setting is extremely rapid, making it extremely limited in practical engineering applications [37]. You N et al [38] found that the amount of steel slag at 50% can significantly delay the setting time of alkali activated mortar and improve the flowability.…”
Section: Introductionmentioning
confidence: 99%